Utilizing Existing Postfeminist Framework to Explore a Sexualized Media Test Case: “Man Needs a Woman” by Maty Noyes (University of Denver Undergraduate Research Journal, 2024)
Postfeminism is simply referred to as the most recent wave of feminism, but feminist scholars have failed to reach a standardized definition that recognizes the nuances of sexuality, media, and culture present within the field. This paper utilizes the postfeminist framework of two prominent feminist scholars: Rosalind Gill and Feona Attwood. Specifically, this paper draws from Gill’s interpretation of postfeminism and Attwood’s interpretation of the sexualization of culture and the overlap between the two theories. Rather than attempt to offer a concrete definition in such a rapidly evolving field, this paper offers a music video from a lesser-known pop artist, Maty Noyes, as a test case to operationalize the theories of Gill and Attwood. The purpose of this work is to evaluate the applicative success of Gill and Attwood while offering an example of the evaluation of a media text as a postfeminism phenomenon.